2000
DOI: 10.1207/s15374424jccp2903_15
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Based Differences Among Boys With ADHD

Abstract: Examined the peer interactions and peer acceptance of three groups of boys ages 8 to 11 1/2 years: attention deficit hyperactivity disorder (ADHD), predominantly inattentive type; ADHD, combined type; and nonclinical controls (N = 45). Peer nominations were obtained from each boy's classroom. Newly acquainted peers consisting of boys from each of the 3 groups were observed for 3 play sessions, after which peer nominations were obtained. Both ADHD groups were more likely than nonclinical controls to receive low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 33 publications
2
125
0
6
Order By: Relevance
“…In fact, researchers have demonstrated that at least one-half of all children with AD/HD are known to have comorbid problems with aggressive conduct (Hinshaw, 1987;Hodgens et al, 2000;Maedgen & Carlson, 2000). Moreover, highly aggressive AD/HD children display severe impairments in the social area, and are strongly rejected by their peers (Gaub & Carlson, 1997;Hinshaw & Melnick, 1995;Hodgens, Cole, & Boldizar, 2000;Landau & Moore, 1991). Studies have shown that children who are prone to intense emotion, especially negative emotion, and are low in regulation are more likely to engage in externalizing behavior associated with negative emotion (Dodge, Lochman, Harnish, Bates, & Pettit, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, researchers have demonstrated that at least one-half of all children with AD/HD are known to have comorbid problems with aggressive conduct (Hinshaw, 1987;Hodgens et al, 2000;Maedgen & Carlson, 2000). Moreover, highly aggressive AD/HD children display severe impairments in the social area, and are strongly rejected by their peers (Gaub & Carlson, 1997;Hinshaw & Melnick, 1995;Hodgens, Cole, & Boldizar, 2000;Landau & Moore, 1991). Studies have shown that children who are prone to intense emotion, especially negative emotion, and are low in regulation are more likely to engage in externalizing behavior associated with negative emotion (Dodge, Lochman, Harnish, Bates, & Pettit, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In general, deficits in aggression and rule breaking behavior may signify one of the primary areas of impairment in AD/HD which eventually result in various problems in peer relationships (Barkley, 2006;Gaub & Carlson, 1997;Hinshaw & Melnick, 1995;Hodgens, Cole, & Boldizar, 2000;Landau & Moore, 1991). Even though a link has been demonstrated between externalizing behavior problems and the presence of social problems in general in western cultures, less work has been done addressing the externalizing behavior problems of children with AD/HD living in non western cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premda socijalni problemi nisu dio dijagnostičkih kriterija za ADHD, poteškoće u odnosima s vršnjacima s kojima se suoča-vaju djeca i mladi s ovim poremećajem rezultiraju učestalim odbijanjem vršnjaka (Hodgens, Cole i Boldizar, 2000;Hoza i sur., 2005;Hoza, 2007). Djeca s ADHD-om pokazuju deficite u socijalnom ponašanju na najmanje tri područja funkcioniranja: agresivno ponašanje, komunikacija i procesiranje socijalnih informacija (Dumas, 1998).…”
Section: Prijateljstvo Djece I Mladih S Teškoćama U Učenjuunclassified
“…In contrast, a lack of emotional regulation skills and over-stimulation frequently result in aggressive, withdrawal, and/or disruptive behaviours (Eisenberg et al, 1994). Furthermore, the social transactions of students with AD/HD are typically characterised by high degrees of conflict (Hodgens, Cole, & Boldizar, 2000), more negative behaviour (Klein & Young, 1979;Pelham & Bender, 1982), fewer friendships (Hinshaw, Henker, & Whalen, 1984), and less popularity among peers (Hinshaw & Melnick, 1995;Hodgens et al, 2000;Maedgen & Carlson, 2000;Pelham & Bender, 1982). In addition, students with AD/HD generally exhibit a higher degree of physical and verbal aggression during their interactions with peers than do students without AD/HD (Hinshaw & Melnick, 1995;Pelham & Bender, 1982).…”
mentioning
confidence: 99%